Assessment of Food Processing Technologies on Allergen Reduction in United States - Williams, Evelyn (International Journal of Food Sciences, 2024)
Purpose: The aim of the study was to analyze the assessment of food processing technologies on allergen reduction in United States. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Recent advancements in food processing technologies in the U.S. are focusing on reducing allergenicity in food products. Thermal methods are traditionally used, but novel nonthermal techniques, such as high-pressure processing and cold atmospheric plasma, are now being explored for their potential to create hypoallergenic products. These methods aim to modify allergenic proteins without using heat, which can preserve food quality while reducing allergen reactivity. Despite these advancements, ensuring the complete removal of allergens remains challenging, highlighting the ongoing need for robust detection and control strategies"‹. Unique Contribution to Theory, Practice and Policy: Risk assessment theory, health belief model (HBM) & diffusion of innovations theory may be used to anchor future studies on analyze the assessment of food processing technologies on allergen reduction in United States. Implementing advanced food processing technologies focused on allergen reduction can revolutionize industry practices. Regulatory bodies could use empirical data from these assessments to set more precise guidelines and safety standards for allergen levels in food products.